Respiratory Morbidity in Prematurely Born Children Receiving Palivizumab Prophylaxis of Respiratory Syncytial Virus Disease - Milena Bjelica; Gordana Vilotijević Dautović; Slobodan Spasojević; Marija Đermanović; Milica Plazačić (Mashhad University of Medical Sciences, 2024)
Background: Preterm delivery is a risk factor for increased respiratory morbidity in early childhood. This study aimed to quantify respiratory morbidity in preterm survivors, comparing incidence rates among different gestational ages, birth weighst, and current age groups. Additionally, we sought to evaluate variations in respiratory outcomes between groups with and without bronchopulmonary dysplasia (BPD). Methods: Our study included 89 prematurely born children who were receiving palivizumab prophylaxis for respiratory syncytial virus infection. We categorized the patients based on four criteria: 1) current age of less and more than 1 year, 2) gestational age (GA) of less and more than 30 weeks, 3) birth weight (BW) of less than 1000 g, between 1000 g and 1500 g, and more than 1500 g, 4) with and without BPD. We compared these groups in terms of respiratory morbidity and respiratory therapy. Results: The average age was 11.9 months, the average GA was 28.9 weeks and the average BW was 1202.4 g. According to the 28-day definition of BPD 75.3% patients had BPD. Around one-third (35.9%) of patients experienced wheezing episodes, 7.8% had pneumonia, 10.1% were hospitalized due to respiratory exacerbation and just 1.1% had RSV infection. There were no statistically significant differences between the different age, GA, BW, or BPD/non-BPD groups in the number of hospitalizations or pneumonia. On the other hand, children older than 12 months and children with BPD had significantly more wheezing episodes. Fifty-nine (66.3%) patients had been receiving inhaled corticosteroids (ICS), all of whom had BPD. Conclusion: Prematurely-born children receiving palivizumab had significant respiratory morbidity, but majority did not have RSV infection. Further clinical studies are necessary to improve our understanding of the role of ICS in patients with established BPD.